2017
DOI: 10.1016/j.jprot.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of human islets collected from frozen pancreata using laser capture microdissection

Abstract: The etiology of Type 1 Diabetes (T1D) remains elusive. Enzymatically isolated and cultured (EIC) islets cannot fully reflect the natural protein composition and disease process of in vivo islets, because of the stress from isolation procedures. In order to study islet protein composition in conditions close to the natural environment, we performed proteomic analysis of EIC islets, and laser capture microdissected (LCM) human islets and acinar tissue from fresh-frozen pancreas sections of three cadaveric donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Two previous studies have utilized LCM and mass spectrometry based proteomics to analyze differential protein expression in human islets obtained under different conditions and pathological states [ 56 57 ]. Unlike our current study, Nishida et al [ 56 ], performed qualitative proteomic analysis to evaluate protein expression using the islets isolated from formalin-fixed paraffin-embedded pancreatic tissues from three autopsied cases of enterovirus-associated fulminant type 1 diabetes (FT1DM) with extensive insulitis compared to five autopsied non-diabetic men.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous studies have utilized LCM and mass spectrometry based proteomics to analyze differential protein expression in human islets obtained under different conditions and pathological states [ 56 57 ]. Unlike our current study, Nishida et al [ 56 ], performed qualitative proteomic analysis to evaluate protein expression using the islets isolated from formalin-fixed paraffin-embedded pancreatic tissues from three autopsied cases of enterovirus-associated fulminant type 1 diabetes (FT1DM) with extensive insulitis compared to five autopsied non-diabetic men.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike our current study, Nishida et al [ 56 ], performed qualitative proteomic analysis to evaluate protein expression using the islets isolated from formalin-fixed paraffin-embedded pancreatic tissues from three autopsied cases of enterovirus-associated fulminant type 1 diabetes (FT1DM) with extensive insulitis compared to five autopsied non-diabetic men. On the other hand, Zhang et al [ 57 ], recently performed comparative quantitative proteomic analyses of enzyme isolated cultured islets, and laser capture microdissected human islets and acinar tissue from fresh-frozen pancreas sections from three non-diabetic cadaveric donors. Unlike these two previous reports, our current proteomics data is obtained from 3 groups of disease stratified phenotype matched comprehensively annotated pancreas tissue samples from nPOD.…”
Section: Resultsmentioning
confidence: 99%
“…There are no studies showing ALK3 expression at the protein level, be it by western blot, proteomics, or immunostaining. In fact, ALK3 has not been detected in proteomic analysis of either human ( Zhang et al, 2017 ) or murine ( Waanders et al, 2009 ) isolated islets. By sorting ALK3 bright+ cells (the only fraction that shows responsiveness to BMP-7), we selectively exclude any residual β cells that may have been carried over in the hNEPT.…”
Section: Discussionmentioning
confidence: 99%
“…This method has the advantage of using frozen tissue, with protein able to be extracted from only the target cell under microscope observation. 34 Previous reports showed that expression of lysosomal enzymes (MDH1, PC and ACLY) involved in glucose sensing tend to be different in human and rat b cells. 35 A proteome analysis focusing on glucose-responsive insulin production, which is a cellular physiological function specific to human pancreatic b cells, was also reported.…”
Section: Discussionmentioning
confidence: 99%